Respon Fagositosis Leukosit Polimorf Babi (in vitro) Terhadap Streptoccocus equi Subsp. Zooepidemicus (PHAGOCYTIC RESPONSE OF SWINE POLYMORPH LEUCOCYTES (IN VITRO) TO STREPTOCCOCUS EQUI SUBSP. ZOOEPIDEMICUS) - Utama, Iwan Harjono; Girindra, Aisjah; Pasaribu, Fachriyan Hasmi; Wibawan, I Wayan Teguh; Setiawan, Endhie D.; Ashadi, Gatut; Rompis, Aida Louise Tenden (Jurnal Veteriner, 2016)
Respon Fagositosis Leukosit Polimorf Babi (in vitro) Terhadap Streptoccocus equi Subsp. Zooepidemicus (PHAGOCYTIC RESPONSE OF SWINE POLYMORPH LEUCOCYTES (IN VITRO) TO STREPTOCCOCUS EQUI SUBSP. ZOOEPIDEMICUS)
Keywords: Streptococcus equi subsp; zooepidemicus; fagositosis